2016
DOI: 10.1109/tcsii.2015.2468924
|View full text |Cite
|
Sign up to set email alerts
|

Synchronizability of Duplex Networks

Abstract: This paper presents some rules and properties about synchronizability of duplex networks composed of two networks interconnected by two links. For a specific duplex network composed of two star networks, analytical expressions containing the largest and smallest nonzero eigenvalues of the (weighted) Laplacian matrix, the interlink weight as well as the network size are given for three different inter-layer connection patterns. It is shown that connection patterns have great influence on the ability of the dupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…More details about supra-Laplacians and multiplex network models can be found in Refs. [18,23,24,29,30] and references therein.…”
Section: Elements L (K)mentioning
confidence: 99%
See 1 more Smart Citation
“…More details about supra-Laplacians and multiplex network models can be found in Refs. [18,23,24,29,30] and references therein.…”
Section: Elements L (K)mentioning
confidence: 99%
“…They may interact on Twitter or on Facebook or on Linked-in or on some combination of all three, and each layer can have its own connectivity pattern, yet there is typically influence propagated between them. Given the need to study dynamical processes on layered complex networks, and the broad applicability of synchronization, here we study synchronization phenomena on multiplex networks, an area that has attracted increasing attention in the past few years [23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, a new type of networks called multilayer networks has been paid increasing attention to. Numerous results indicate that interaction between networks can greatly affect dynamics on interacting networks, such as spreading, diffusion and synchronization [24,[31][32][33][34][35][36][37][38][39][40][41][42]. For example, in 2014, Aguirre et al [32] investigated the influence of the connector node degree on the synchronizability of two star networks with one inter-layer link and showed that connecting the high-degree (low-degree) nodes of each network is the most (least) effective way to achieve synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, synchronization of all dynamical nodes in a network, as an interesting and significant topic, has drawn special attention. Many efforts have also been to address the synchronization problem of complex networks [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%